A federated approach for global village services interaction - Mollahoseini Ardakani, Mohammad Reza; Hashemi, Seyyed Mohsen (Journal of Advanced Computer Science & Technology, 2014)
In the global village ecosystem, enterprises need collaborating using Information Technology (IT) and other tools to succeed in this dynamic and heterogeneous business environment. The Global Village Services Reference Model (GVSRM) is a reference model based on SOSA (Service Oriented Strategies and Architectures) ontology for global village services Realization. In this model, three architectural abstraction layers have been considered for global village: ‘infrastructure for global village services’, ‘global village services provisioning’, and ‘using global village services’. Despite relative completeness of this model, one of its obvious shortcomings is lack of attention to the crucial issue of interoperability in the global village. Based on this model, the grid of global village is comprised of VHGs (Virtual Holding Governance). The VHG is a temporary, scalable, dynamic cluster/association comprising of existing or newly service provider organizations which its objective is satisfying the requirements of global village actors through electronic processes. In this paper, we will propose a federated approach for interoperability among the VHGs of the global village. Keywords: Collaboration, Global Village, GVSRM, Interoperability, Virtual Holding Governance (VHG).